Clinical and histological response of human pulp tissue to direct pulp capping with mineral trioxide aggregate, Biodentine and propolis - Zahra Nasri; Maryam Zare Jahromi; Atousa Aminzadeh (Wolters Kluwer Medknow Publications, 2022)
Background: This study clinically and histologically compared the human pulp response to direct pulp capping (DPC) with mineral trioxide aggregate (MTA), Biodentine, and propolis in 2 months. Materials and Methods: In this clinical trial evaluated 41 premolars candidate for extraction due to orthodontic purposes of patients between 15 and 25 years of age. A group of 5 was separated randomly as the negative control. The remaining teeth were randomly divided into three experimental groups of 12 after mechanical exposure of the pulp by bur in high-speed handpiece under air and water spray. The exposed areas were capped with MTA, Biodentine, or propolis. Glass ionomer was applied as base over the cap. The teeth were restored with composite resin. Patients were recalled in 2 months for clinical and radiographic examinations and also pulp vitality test. Teeth were then extracted. Slides were prepared and tissue sections were evaluated for the presence and severity of inflammation, dentinal bridge, and continuity. Data were analyzed using the Chi-square and Fisher's exact tests. Results: The clinical success rate was 100% in the MTA and 91.7% in both the propolis and Biodentine groups. The presence and severity of pulpal inflammation and dentinal bridge formation were similar in all the experimental groups (P > 0.05). Dentinal bridge formation was similar in the MTA and Biodentine groups and was higher than in the propolis group. Continuation of dentinal bridge in the MTA group was significantly higher than that in the Biodentine and propolis groups (P < 0.05). Conclusion: MTA, Biodentine, and propolis are equally effective for DPC.